تاثير منهج تدريبي بالاسلوب المتعاقب على بعض المتغيرات البدنية والمهارية للحركات الارضية في الجمناستك الفني للطلاب - دهام, أميرة محمد; عبدالواحد, حبيبه نهاد (Sulaimani Journal for Humanities, 2022)
Extract The aim of the search is to: 1. Preparing exercises in a successive manner for the subject of artistic gymnastics for students of the third stage, such as physical education, Koya University. 2. Recognizing the effect of exercises in a successive manner on some of the physical and skill variables of floor movements in gymnastics for the research sample. 3. Identifying the differences between the use of training in the successive method and the method followed by the teacher in some physical and skill variables of floor movements in gymnastics for the research sample. The research hypotheses were: 1. There are statistically significant differences between the results of the tribal and remote tests for the experimental and control groups in some physical and skill variables of the ground movements of the artistic gymnastics for the research sample. 2. There are statistically significant differences for the results of the post-tests between the two experimental groups that use the successive method of training, and the control group that uses the method followed by the teacher in some physical variables and the skills of the floor movements of the artistic gymnastics for students of the two categories of physical education, Koya University. The researchers used the experimental method for its relevance to the research problem, and the research sample and society consisted of students of the third stage of the two faculty of physical education / Koya University for the academic year 2021-2022, numbering (24 students), and the sample was chosen in a deliberate way and divided into two experimental and control groups, totaling (20 students) and thus The percentage is 83.3% (4 students) were used in conducting the exploratory experiment.The researchers used the international information network, Arab and foreign sources and references, and questionnaires for the opinions of experts and specialists about evaluating the technical performance of the floor movements in gymnastics, physical variables and skill performance, and tests were determined The sprint test for a distance of 50 yards, the explosive power test for the legs, the speed characteristic test for the arms, the stretching test for the abdominal muscles, the oblique prone test from standing (agility) (10 seconds), and the skill tests included (bending back roll, Arab jump, Kartwell, handstand, front rolling) and the performance was evaluated by three arbitrators, where the degree for each skill was 10 degrees, and the arithmetic mean of the three arbitrators was extracted. The training curriculum was applied directly to the experimental group over a period of 6 weeks, with 4 lessons per week, then the post-tests were conducted, and the researchers reached the following conclusions: The physical abilities of both groups developed as a result of the nature and similarity of the exercises There were no significant differences between the post tests in the physical abilities of both groups The cross-training had a great impact on the development of the ground movements of the experimental group In light of the conclusions reached by the researchers, the researchers recommend - Adoption of the training curriculum in a successive manner in the subject of gymnastics for students of the third stage, such as physical education, Koya University. - Intensifying physical exercises similar to kinetic performance in gymnastics and paying attention to the physical aspects of students and developing them, due to the peculiarity of gymnastics, which needs special and high physical specifications to perform its skills in a correct technical manner. - Conducting similar researches to apply the training curriculum in a successive manner in gymnastics for third-year students, such as physical education, Koya University.